Quantitative measurement of axial accumulation of red blood cells in micro channel using micro PTV - Kinoshita, Haruyuki; Charalambides, Alexandros; Yabusaki, Hitoshi; Oishi, Masamichi; Oshima, Marie (Journal of the Visualization Society of Japan, 2007)
In order to elucidate the effect of red blood cell (RBC) on blood flow at low Reynolds number, the paper aims to examine both distributions and velocity profiles of hardened RBCs in a micro channel varying experimental conditions such as shape and particle Reynolds number. We compare distributions and velocity profiles of both hardened RBCs and spherical particles in a micro channel using a micro PTV (particles tracking velocimetry) system. The micro PTV system consists of a fluorescent microscope equipped with a CMOS camera. Fluorescently-labeled hardened RBCs are suspended in saline within a 100μm square micro channel. In the paper, binarization method with dynamic threshold is applied since the intensity of labeled hardened RBC in the PTV images is too low to calculate the positions and velocities of RBCs. Both the flow velocity profiles and distributions of hardened RBCs are compared with those of the particles in order to clarify the effect of RBC biconcave shape.